Zapisz w jak najprostszej postaci postaci:
a) √7² + √6 - (√6)² =
b) ∛12³ - (√17)² - √5 =
c) 3√5² + 2√5 - 2∛(-5)³=
d) -∛5³ - ∛7 - ∛-7=

e) 8√7 + √7 =
f) 10 + 5√6 - 2√6=
g) 2√13 - 1 + √13=
h) 3∛10 - ∛10=
i) -∛5 + ∛-5=
j) 3∛9 - ∛-9=

Bardzo dziękuję za pomoc :)
Pozdrawiam !

3

Odpowiedzi

2010-03-01T11:58:55+01:00
A) √7² + √6 - (√6)² = 7 + √6 - 6 = √6
b) ∛12³ - (√17)² - √5 = 12 - 17 - √5= -5 - √5
c) 3√5² + 2√5 - 2∛(-5)³=3*5 + 2√5 - 2*5= 15+ 2√5 -10 = 5+ 2√5
d) -∛5³ - ∛7 - ∛-7=-5- ∛7 - ∛-7
e) 8√7 + √7 = 9√7
f) 10 + 5√6 - 2√6= 10+ 3√6
g) 2√13 - 1 + √13= -1 +3√13
h) 3∛10 - ∛10=2∛10
i) -∛5 + ∛-5=1
j) 3∛9 - ∛-9=2∛9






3 5 3
2010-03-01T12:00:37+01:00
A) √7² + √6 - (√6)² = 7
b) ∛12³ - (√17)² - √5 =12 - 17 = 5
c) 3√5² + 2√5 - 2∛(-5)³=
d) -∛5³ - ∛7 - ∛-7= -5 - 2∛-7

e) 8√7 + √7 = 9√7
f) 10 + 5√6 - 2√6= 10 + 3√6
g) 2√13 - 1 + √13=3√13 - 1
h) 3∛10 - ∛10=2∛10
i) -∛5 + ∛-5=0
j) 3∛9 - ∛-9=2∛-9

Mam nadzieję, iż pomogłem, jeżeli ta to proszę o Naj ;)
2 1 2
2010-03-01T12:08:06+01:00
A]√7²+√6-(√6)²=7+√6-6=√6+1
b]∛12³-(√17)²-√5=12-17-√5=-5-√5=-5(1+√5)
c]3√5²+2√5-2∛(-5)³=∛25+2√5+10
d]-∛5³-∛7-∛-7=-5-∛7-∛-7=5+∛-7-∛-7=5+2∛-7
e]8√7+√7=9√7
f]10+5√6-2√6=10+3√6
g]2√13-1+√13=3√13-1
h]3∛10-∛10=2∛10
i]-∛5+∛-5=∛-5+∛-5=2∛-5
j]3∛9-∛-9=3∛9+∛9=4∛9
2 5 2